Development of problem-based learning teaching modules to facilitate the mathematical communication skills of grade VII junior high school students - Abdullah, Sulaiman; Hutapea, Nahor Murani; Kartini, Kartini (Jurnal Gantang, 2026)
This study aimed to develop a Problem-Based Learning (PBL) module on flat-sided solid shapes to facilitate the mathematical communication skills of eighth-grade junior high school students. The study employed the 4-D development model consisting of four stages: define, design, develop, and disseminate. The research was conducted in class VIII C of SMPN 1 Rumbio Jaya with 30 students. The results indicated that the PBL-based teaching module was highly valid, achieving average validation scores of 95% for the teaching module, 94% for the student worksheet (LKPD), and 94% for the learning assessment. Practicality testing also showed very practical results, with average scores of 85% in small-group trials and 88% in large-group trials. The findings demonstrate that the developed module effectively facilitates students' mathematical communication skills. Through the PBL phases embedded in the LKPD, students were guided to identify and analyze problems, represent ideas using mathematical symbols and diagrams, and communicate their reasoning in written form. These activities supported the development of key mathematical communication indicators, particularly students' abilities to express mathematical ideas through writing and visual representations.